What were the changes during the COVID-19 pandemic era concerning occupational risks among health care workers? - Husrev Diktas; Ahsen Oncul; Ceren Atasoy Tahtasakal; Dilek Yıldız Sevgi; Ozlem Kaya; Nese Cimenci; Nuray Uzun; Ilyas Dokmetas (Elsevier, 2021)
Background: Accidental exposure to percutaneous needle stick and sharp injuries (NSSIs) and blood and other body fluids is the unintended contact with risky medical instruments or patient secretions during a medical intervention. During the COVID-19 pandemic, the significance of occupational injuries in healthcare professionals was revealed once again. To assess the occupational injuries, we compared rates, distribution and type of exposure to blood and body fluids and NSSIs of health care workers for 2019 (pre-pandemic era) and 2020 (pandemic era) years, respectively. Material and methods: Our study included data collected by the 'Hospital Infection Control Committee' for the years 2019-2020. Data collected using the active surveillance method were analyzed retrospectively. Results: During 2019 (pre-pandemic period) and 2020 (pandemic period), 112 (27.65%0) and 82 (21.4%0) NSSIs reported, respectively. Of the exposed HCWs in 2019 (pre-pandemic period), 16.8%0 (14) were doctor, 53.6%0 (60) were nurse and 47.4%0 (14) were intern doctors. In the 2020 (pandemic period), NSSIs were observed most frequently in nurses and cleaning staff, 50.24%0 and 33.64%0, respectively. Concerning the total percentage of exposure to blood and other body fluids, a slight increase was revealed from 1.48%0 to 2.62%0 in 2019 and 2020, respectively. A significant decrease in exposure rate was reported among the doctors between the pre-pandemic and pandemic era; 3.6%0 and 1.19%0 at 2019 and 2020, respectively. A significant increase in exposure rate was reported among the nurses between pre-pandemic and pandemic era; 0.8%0 and 6.89%0, respectively. Conclusion: In conclusion, the exposure to NSSIs during the pandemic period decreased; however, there was no severe difference at pre-pandemic and pandemic periods concerning exposure to blood and body fluids. Well-designed training and awareness programs can be effective in preventing exposure to NSSIs and blood and other body fluids and exposure to respiratory acquired viruses.